2018
DOI: 10.1039/c7sc05420c
|View full text |Cite|
|
Sign up to set email alerts
|

Rapid access to diverse, trifluoromethyl-substituted alkenes using complementary strategies

Abstract: Herein describes two complementary methods, a one-step cross-coupling and the functionalization of a ‘masked’ functionality, to access diverse trifluoromethyl alkenes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 43 publications
0
16
0
Order By: Relevance
“…Trifluoromethyl-substituted alkenes 2 were initially selected for exploring the proposed cyclopropanation given their known compatibility with photoredox catalysis and proficiency as radical acceptors. , In addition, success here would allow the mild, one-step preparation of valuable TFCps 3 from trifluoromethyl-substituted alkenes. Given the ease with which these olefins can now easily be accessed from commercially available trifluoromethyl ketones, aryl halides, or organoboron reagents, success here would provide a regiospecific means to install the TFCp motif on virtually any scaffold (arene, hetereoarene, aliphatic, etc., Figure ).…”
Section: Discussionmentioning
confidence: 99%
“…Trifluoromethyl-substituted alkenes 2 were initially selected for exploring the proposed cyclopropanation given their known compatibility with photoredox catalysis and proficiency as radical acceptors. , In addition, success here would allow the mild, one-step preparation of valuable TFCps 3 from trifluoromethyl-substituted alkenes. Given the ease with which these olefins can now easily be accessed from commercially available trifluoromethyl ketones, aryl halides, or organoboron reagents, success here would provide a regiospecific means to install the TFCp motif on virtually any scaffold (arene, hetereoarene, aliphatic, etc., Figure ).…”
Section: Discussionmentioning
confidence: 99%
“…From the perspective of Si−O bond activation, weakening of Si−O bonds is of considerable significance regarding the conversion of silicates to silanes. Especially dicatecholato‐silicate(IV) complexes are frequently used as precursors for either silane synthesis or functionalization of various organic molecules . Most recently, a collaborative research of Ollivier and co‐workers together with Fensterbank and co‐workers demonstrated a new synthesis for ketones, in this context employing acyl chlorides …”
Section: Introductionmentioning
confidence: 99%
“…Especially dicatecholato-silicate(IV) complexes are frequently used as precursors for either silane synthesis or functionalization of various organic molecules. [35][36][37][38][39][40][41][42][43] Most recently,acollaborative research of Ollivier and co-workerst ogether with Fensterbank and co-workers demonstrated an ew synthesis for ketones,i nt his context employinga cyl chlorides. [44]…”
Section: Introductionmentioning
confidence: 99%
“…As a part of our ongoing interest in carbene catalysis, we herein disclose a new strategy for the synthesis of enantiopure fluoromethyl-substituted chromenones via a one-pot carbene-catalyzed umpolung/oxidation process (Scheme ). After the formation of the Breslow intermediate I by the carbene catalyst with the aldehyde, the CF 3 - or CF 2 H-tethered moderately electron-poor double bond underwent an intramolecular proton transfer to give the hydroacylation intermediate II . The release of the carbene and oxidation of 3 finally delivered the chromenone containing a fluoromethyl-substituted stereogenic center.…”
mentioning
confidence: 99%
“…Trisubstituted alkene 1a′ with the Z configuration ( E / Z < 5:95) was first subjected to the reaction conditions (Scheme , eq 3), the reaction delivered the product ( R )- 2a in high yield and ee, in contrast with the result of the model substrate 1a ( E / Z > 95:5) which afforded ( S )- 2a . This observation implied an intramolecular proton transfer from the OH group of the Breslow intermediate to the terminal carbon atom of the double bond during the reaction process . These assumptions are supported in part by the isolation of deuterated 4H-chromenone derivative 2a-D from the reaction mixture when deuterated 1a-D was used as the substrate under the same conditions (Scheme , eq 4).…”
mentioning
confidence: 99%